2000
DOI: 10.1007/s002130000601
|View full text |Cite
|
Sign up to set email alerts
|

Kappa-opioid receptors and relapse-like drinking in long-term ethanol-experienced rats

Abstract: Stimulation of kappa-opioid receptors can increase ethanol intake, at least in long-term ethanol-experienced rats. Since kappa-opioid receptor agonists have aversive motivational consequences, increased ethanol drinking might be an attempt to counteract the aversive effects of this treatment. On the other hand, the nor-BNI experiments indicate that endogenous kappa-opioid receptor stimulation does not seem to be involved in relapse-like drinking after protracted abstinence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
88
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(109 citation statements)
references
References 38 publications
17
88
4
Order By: Relevance
“…Chronic administration of naltrexone alone or in combination with acamprosate eliminated this deprivation-induced increase in drinking. These results confirm previous reports that opiate antagonists and acamprosate reduce the alcohol deprivation effect (Hölter et al, 1997;Spanagel et al, 1996a;Heyser et al, 1998;Hölter and Spanagel, 1999;Hölter et al, 2000). In the present study, the effects of drug administration had no effects on responding for water.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Chronic administration of naltrexone alone or in combination with acamprosate eliminated this deprivation-induced increase in drinking. These results confirm previous reports that opiate antagonists and acamprosate reduce the alcohol deprivation effect (Hölter et al, 1997;Spanagel et al, 1996a;Heyser et al, 1998;Hölter and Spanagel, 1999;Hölter et al, 2000). In the present study, the effects of drug administration had no effects on responding for water.…”
Section: Discussionsupporting
confidence: 93%
“…These results confirm previous reports that opioid receptor antagonists reduce ethanol intake (Samson and Doyle, 1985;Hubbell et al, 1986;Froehlich et al, 1990;Weiss et al, 1990;Hyytia and Sinclair, 1993;June et al, 1999) and attenuate the ethanol deprivation effect (Hölter and Spanagel, 1999;Hölter et al, 2000). The reduction in responding for ethanol below baseline observed after administration of the higher doses (0.125 and 0.25 mg/kg) of naltrexone was specific to the first day after ethanol deprivation.…”
Section: Discussionsupporting
confidence: 91%
“…Natural and synthetic kappaopioid receptor agonists directly infused into the striatum or administered systemically to rodents will both attenuate cocaine-induced dopamine surges in the nucleus accumbens and block cocaine-induced conditioned place preference (Maisonneuve et al, 1994;Zhang et al, 2004a, b). Centrally penetrating kappa-opioid receptor agonists can be aversive in rodents, so studies showing a reduction in alcohol intake but an increased alcohol deprivation effect and a decrease in morphine and cocaine self-administration may be difficult to interpret (Glick et al, 1995;Hölter et al, 2000;Lindholm et al, 2001). Studies of kappa-opioid receptor antagonists have not found an effect of these agents on alcohol, morphine, or cocaine administration (Glick et al, 1995;Hölter et al, 2000).…”
Section: Mu-and Kappa-opioid System and Addictionmentioning
confidence: 99%
“…Centrally penetrating kappa-opioid receptor agonists can be aversive in rodents, so studies showing a reduction in alcohol intake but an increased alcohol deprivation effect and a decrease in morphine and cocaine self-administration may be difficult to interpret (Glick et al, 1995;Hölter et al, 2000;Lindholm et al, 2001). Studies of kappa-opioid receptor antagonists have not found an effect of these agents on alcohol, morphine, or cocaine administration (Glick et al, 1995;Hölter et al, 2000). Acute administration of cyclazocine or butorphanol, compounds with mixed activity at mu-and kappa-opioid receptors, in human cocaine users did not alter the effects of investigator-administered intranasal cocaine or reduce intravenous cocaine self-administration (Walsh et al, 2001;Preston et al, 2004).…”
Section: Mu-and Kappa-opioid System and Addictionmentioning
confidence: 99%
“…Even though there is no report regarding the effects of prenatal alcohol exposure on kappa mRNA level in fetal animal models, experimental animal data have documented significant interactions between the kappa opioid receptor and alcohol use in adulthood. [36][37][38][39] Prenatal alcohol exposure in humans has in fact been shown to be most predictive of adolescent alcohol use even after adjusting for family history and other prenatal and environmental variables, 40 which suggests that modification of the kappa system by prenatal alcohol exposure could have a long-lasting effect on behavior that enhances the vulnerability to alcoholism. It is interesting to note that alcohol-related changes on the kappa opioid receptor mRNA were not mimicked by alterations in the PDYN mRNA expression.…”
Section: Discussionmentioning
confidence: 99%